2021
DOI: 10.18203/2394-6040.ijcmph20211393
|View full text |Cite
|
Sign up to set email alerts
|

Atopic triad (allergic rhinitis, eczema, and asthma) and eye rubbing as risk factors for keratoconus: a systematic review and meta-analysis

Abstract: Keratoconus (KN), is an eye disorder, characterized by progressive thinning and protrusion of central cornea. A number of conditions such as such as allergy, asthma, eczema, and eye rubbing has been shown to be associated with the development of KN. However, there is a disagreement regarding some of risk factors and their strength so we conducted systematic review and meta-analysis to determine how strongly risk factors such as eye rubbing, and atopic triad associate with KN development and progression. We sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Our research findings show an odd ratio (OR) of 3.6 with a p- value less than 0.001 for eye rubbing ( Table 2 ). Several studies reported a strong association between eye rubbing and KC [ 12 , 13 ], whilst other authors reported no association between eye rubbing and KC [ 14 , 15 ]. The differences among these studies could be related to how UCHER or abnormal eye rubbing was classified.…”
Section: Discussionmentioning
confidence: 99%
“…Our research findings show an odd ratio (OR) of 3.6 with a p- value less than 0.001 for eye rubbing ( Table 2 ). Several studies reported a strong association between eye rubbing and KC [ 12 , 13 ], whilst other authors reported no association between eye rubbing and KC [ 14 , 15 ]. The differences among these studies could be related to how UCHER or abnormal eye rubbing was classified.…”
Section: Discussionmentioning
confidence: 99%